Pelatihan Asuhan Keperawatan Spiritual Menggunakan SDKI, SLKI dan SIKI Melalui Teleconference Bagi Perawat dan Bidan RSUD Depok - Murtiningsih Murtiningsih; Nedra Wati Zaly; Dyah Fitri Wulandari; Ade Suhendri (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
This community service activity was carried out in collaboration with STIKes Jayakarta and RSUD Depok. Based on initial data when providing nursing care to 12 Muslim patients, it was found that 4 out of 12 patients (33%) did not pray with the reason is that a urinary catheter was attached, did not bring prayer equipment, could not perform wudhu to the bathroom, and did not pray before being sick.. Nurses are expected to be able to fullfill patient needs comprehensively biology, psychology, social-spiritual, but spiritual needs have not been fully fulfilled. The fulfillment of spiritual needs related to worship is of course given according to the religion of each individual. Nurses can act as facilitators in fullfill spiritual needs. Increasing knowledge of nurses related to competence in fullfill the spiritual needs of patients treated in hospitals, including through training activities for spiritual nursing care. The form of activity is in the form of spiritual nursing care training using the guidebook from the Indonesian National Nurses Association (PPNI), namely the Indonesian Nursing Diagnosis Standard (SDKI), the Indonesian Nursing Outcome Standard (SLKI), and the Indonesian Nursing Intervention Standard (SIKI). The training was conducted through teleconference, starting with lectures and discussions as well as video showings related to the procedures for facilitating worship of patients treated in hospitals. The training was given to nurses and midwives who were divided into 3 stages alternately with a total of 127 participants. The result of this activity is an increase in knowledge and skills about spiritual nursing care, then the formation of a whatsapp group for guidance, the application of spiritual nursing care in their ward, spiritual nursing care modules, patient worship guides, videos of patient worship procedures.